The process of formation of religious members in the church: a case study of the Institute of the Blessed Virgin Mary - Awiti, Marren Rose A. (Peter Lang, 2019)
Formation during the period of temporary vows in religious institutes in the canonical tradition -- Formation during the period of temporary vows according to the 1983 Code and the subsequent documents -- Formation during the period of temporary vows in the Institute of the Blessed Virgin Mary (Loreto Sisters) -- Assessment of conformity in the implementation of proper law of the Institute of the Blessed Virgin Mary (Loreto Sisters) to the universal law on formation during the period of temporary vows -- General conclusions